Is Literacy Improving the Intention of The Younger Generation to Use Islamic Non-Bank Financial Products? - Sugianto Sugianto; Andri Soemitra; Sri Sudiarti; Nur Amadi Bi Rahmani (Institut Agama Islam Negeri Padngsidimpuan, 2022)
The banking industry has historically dominated Islamic financial institutions. In fact, Non-Bank Financial Institutions (NBFIs) provide alternatives for the public's different financial needs. For Islamic Non-Bank Financial Institutions, the youthful Muslim generation is a very promising target market. The goal of this study is to see whether literacy can improve young Muslims' intention to use Non-Bank Financial Institutions' products. On 138 Muslim youngsters in North Sumatra, this study takes a quantitative method with simple linear regression analysis. The study's findings show that literacy has a positive and significant impact on the younger generation of Muslims' intentions to use Islamic Non-Bank Financial Institutions products. Socialization and education, both formal and informal, are important elements in raising the literacy of Muslims' younger generations.